Dynamic intellectual capital model in a company - Shatrevich, Vladimir; Ščeulovs, Deniss; Gaile-Sarkane, Elina (Business, Management and Economics Engineering, 2015)
The aim of this paper is to indicate the relations between company’s value added (VA) and intangible assets. Authors declare that Intellectual capital (IC) is one of the most relevant intangibles for a company, and the concept with measurement, and the relation with value creation is necessary for modern markets. Since relationship between IC elements and VA are complicated, this paper is aimed to create a usable dynamic model for building company’s value added through intellectual capital. The model is incorporating that outputs from IC elements are not homogeneously received and made some contributions to dynamic nature of IC relation and VA. Variables that will help companies to evaluate contribution of each element of IC are added to the model. This paper emphasizes the importance of a company’s IC and the positive interaction between them in generating profits for company.